Pengaruh Story Telling Terhadap Kecemasan Anak Usia Pra Sekolah Dalam Menghadapi Hospitalisasi di Ruang Rawat Inap Paviliun Cemara RSUD Siti Fatimah Provinsi Sumatera Selatan Tahun 2025: Penelitian - Yora Nopriani; R. Rembulan Eka Yulien (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Preschool-aged children are those between 3 and 6 years old. At this age, children are very active and often engage in various activities, but their immune systems are still not fully developed. As a result, they are more susceptible to illness and may need to undergo hospital procedures, known as hospitalization. Hospitalization often causes fear in children and can trigger anxiety. If this anxiety is not addressed, it can have negative effects and hinder the child’s care process in the hospital. Storytelling is one method that can be used to help reduce anxiety in children. Objective: This study aimed to determine the effect of storytelling intervention on the anxiety levels of preschool-aged children undergoing hospitalization. Methods: This quantitative study used a quasi-experimental design with a one-group pretest-posttest approach. Data analysis was performed using the Wilcoxon Signed Rank test on 32 respondents. Results: The results showed a p-value of 0.001 < α 0.05. The mean anxiety level before the storytelling intervention was 49.5, which decreased to 33 after the intervention. This indicates a reduction in anxiety levels among preschool-aged children following the storytelling intervention.